A secured openflow protocol using Elliptic Curves Cryptographic for software defined networks - Khalil Al Dulaimi, L.A.; Badlishah Ahmad, R.; Yaakob, N; Hussein, Q.M. (2018)
A Software-Defined Network (SDN) architecture was proposed to enhance the performance, flexibility and scalability of networks. However, SDN features such as centralized controlling, network programmability and virtualization present new security challenges to networks. This article will address security challenges related to SDN connection data transfer channels (i.e., control layer and infrastructure layer) and propose a novel connection data transfer channels architecture based on an OpenFlow protocol. Existing SDN OpenFlow protocols rely on higher layer secure mechanisms such as TLS (Transport Layer Security) / SSL (Secure Sockets Layer) sessions. It is concluded that the transfer of secured data using elliptical curve encryption provides a more efficient SDN network. The proposed architecture was implemented in a testbed and its security features were analyzed.